Impact of chronic kidney disease on platelet P2Y12 receptor signalling in patients with type 2 diabetes mellitus - Engwenyu, Lydia R.; Franchi, Francesco; Rollini, Fabiana; Cho, Jung Rae; DeGroat, Christopher; Bhatti, Mona; Alobaidi, Zeina; Ferrante, Elisabetta; Jakubowski, Joseph A.; Sugidachi, Atsuhiro; Zenni, Martin M.; Bass, Theodore A.; Angiolillo, Dominick J. (Thrombosis and Haemostasis, 2017)
Supplementary Material to this article is available online at www.thrombosis-online.com.